Prevalence and Scabies Severity Rate on a Goat at Mempawah Hilir, Mempawah District West Kalimantan Province - Arum Maula Hidayah; Wiwiek Tyasningsih; Soeharsono Soeharsono; Retno Wulansari (Journal of Parasite Science (JoPS), 2021)
This research aims to determine the prevalence and severity rate of scabies on goats in Sub-District of Mempawah Hilir, Mempawah, West Kalimantan. The goat livestock used were not determined by age, sex, and breed. The number of goats researched was 100 goats. Scabies prevalence measurement was to divide the number of scabies goats by total goats, then multiplied by 100% and measurement of the severity rate of scabies goats with scoring with grades 1-3 (low), 4-6 (moderate), and 7-9 (heavy). The results obtained scabies prevalence rate of 38% with 38 positive samples from a population of 100 goats and the percentage of severity was 42%, moderate 24%, and 34% severe. This is due to weather factors in the area and the type of cage as well as inadequate maintenance management, thus making many cases of scabies attack goats.